Istiqra ’Illah al-Qital fi al-Islam - Naseh Alwan, Ammar Abdullah (Jurnal Fiqh, 2009)
This study investigates ’illa (underlying reason or the rationale) of Jihad (holy fighting in All?h`s Cause) in Islam. The novelty of the study lies in tackling the issue whether that non-Muslims should be fought against merely because they are disbelievers, not because of attacking Muslims or the message they are trying to convey. Through the deduction approach of shari’yah texts especially Quranic ones concerning Jihad and its fiqh rules, the study demonstrates that the approach of those who think that ’illa of fighting in Islam is disbelieving is a dangerous way of thinking because it has a kind of compulsion in religion unlike what the Qur`an ct